Equipment provision after stroke: A scoping review of the use of personal care and mobility aids in rehabilitation. (February 2017) - Boland, Pauline; Levack, William; Perry, Meredith; Graham, Fiona
Introduction: The aim of this scoping review was to examine and synthesise literature on adaptive equipment use for personal care and mobility after stroke. Method: We searched databases including Medline, EMBASE, AMED, CINAHL and Scopus to February 2016. Two authors independently screened 789 titles, identifying 28 studies for inclusion in the review. Results: Findings were grouped into four themes: (1) stroke-specific impairments and consequences for equipment use and training; (2) meaning of equipment for people with stroke; (3) cost of equipment after stroke; and (4) conflicts between equipment provision and models of stroke rehabilitation. Conclusion: The wide range of impairments after stroke increases complexity of how people use equipment. Nonetheless, training needs and the relationship between social context, identity and equipment use are increasingly better understood, . The findings highlight a tension between practice that seeks to re-train function by 'normal' movement without equipment and restoration of function by using compensation strategies involving use of equipment. However, there is no evidence that compensation strategies impede recovery of physical abilities. High-quality evidence about costs of equipment after stroke, which could inform policy decisions, is urgently needed.